Dermocosmetics in the management of Acne Vulgaris - Mich, Anna; Ciesielski, Radosław; Perkowska, Klaudia; Kaźmierczak, Anna; Izdebska, Wiktoria; Sornek, Patrycja; Borkowska, Agata; Kiełb, Anna; Pawlak, Igor; Stanek, Jakub (Quality in Sport, 2024)
Treating acne vulgaris remains a significant challenge for dermatologists. Dermocosmetics are becoming an essential component of acne management. The active ingredients in dermocosmetics help support dermatological treatments, while gentle formulations help maintain the skin’s lipid barrier, reduce transepidermal water loss, and minimize the risk of irritation. Our objective was to review the active ingredients and various preparations used in dermocosmetics for acne, and to emphasize the clinical evidence supporting their effectiveness.